Cardiac troponin T quantitative assay failure as a result of antibody interference - Philip H. Fortgens; Fierdoz Omar (AOSIS, 2013)
Background: Immunoassays are prone to interference by various substances which may cause inaccurate results. This type of interference is difficult to detect analytically. Objective: A case of CARDIAC Troponin T Quantitative reader (Roche Diagnostics) assayfailure was detected and investigated in order to ascertain the likely cause. Method: Patient whole blood was mixed with cardiac troponin T-positive blood, patient and control sera were denuded of immunoglobulin G by protein A-affinity chromatographyand patient sera were mixed with mouse serum. Samples were analysed on a CARDIAC Troponin T Quantitative reader. Results: A mixture of patient whole blood and cardiac troponin T-positive blood resultedin assay failure; removal of immunoglobulin G from patient sera reversed the cardiactroponin T assay failure; the addition of mouse serum as a heterophile antibody blocking agent had no effect. Conclusion: It is proposed that the interference resulting in assay failure may not be because of a heterophile antibody, but rather a result of a circulating autoantibody to cardiactroponin T, which may compete with antibody assay reagents for binding sites.